1980
DOI: 10.1029/jc085ic04p01910
|View full text |Cite
|
Sign up to set email alerts
|

The Batchelor spectrum and dissipation in the upper ocean

Abstract: Observations of vertical temperature microstructure at ocean station P during the mixed layer experiment (Mile) indicate that the shape of the high-frequency temperature gradient spectrum depends on the relative strengths of turbulence and stratification. For low Cox number ((dT/dz) 2) /(dT/dz) • the linear range of the Batchelor spectrum is not well approximated by observed spectra, while for high Cox number a remarkably close correspondence to the Batchelor spectrum is found. Dissipation rates calculated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
152
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 20 publications
10
152
0
Order By: Relevance
“…Dissipation rates are generally lower in offshore areas and are unlikely to induce a larval sinking response, even during moderate storms. In winds ഠ15 m s Ϫ1 , dissipation rates at the surface and thermocline reach ϭ 10 Ϫ3 -10 Ϫ2 cm 2 s Ϫ3 (Dillon and Caldwell 1980), but our larvae rarely sank at Յ 10 Ϫ2 cm 2 s Ϫ3 . Although stormy conditions at sea could cause some veligers to sink (Barile et al 1994), we expect that larvae will encounter and respond to strong turbulence primarily in nearshore areas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissipation rates are generally lower in offshore areas and are unlikely to induce a larval sinking response, even during moderate storms. In winds ഠ15 m s Ϫ1 , dissipation rates at the surface and thermocline reach ϭ 10 Ϫ3 -10 Ϫ2 cm 2 s Ϫ3 (Dillon and Caldwell 1980), but our larvae rarely sank at Յ 10 Ϫ2 cm 2 s Ϫ3 . Although stormy conditions at sea could cause some veligers to sink (Barile et al 1994), we expect that larvae will encounter and respond to strong turbulence primarily in nearshore areas.…”
Section: Discussionmentioning
confidence: 99%
“…Many larvae settle preferentially on particular sediments (Snel- Dillon and Caldwell (1980) Oakey and Elliott (1982) Nowell (1985) George et al (1994) Fig. 1.…”
mentioning
confidence: 99%
“…K ρ is ill defined in the absence of stratification and we exclude the segments with N < 1.7×10 −3 s −1 equivalent to one cycle per hour (cph). The eddy diffusivity for heat is obtained from the iso- Osborn and Cox, 1972), using the dissipation rate of thermal variance, (Dillon and Caldwell, 1980), constrained by the measured ε, to the resolved wavenumber band of the T-gradient spectrum over 4 m segments. The noise level for ε is 5−7×10 −10 W kg −1 , only adequate to resolve the turbulence in the upper 200 m, but χ is resolved throughout the profiling depth.…”
Section: Sampling and Processing Detailsmentioning
confidence: 99%
“…It should be noted that this is an indirect inference of turbulence (Thorpe 2005). In a study on marine snow thin layers (Alldredge et al 2002), the turbulent kinetic energy (TKE) dissipation rate, ε, was estimated using the spectra expected for temperature microstructure (Dillon & Caldwell 1980). It was observed that dissipation rate in the thin layer was very low, ε < 10 -8 W kg -1…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%